Melanomacrophage centeres and diseases occurring in lesser-spotted catsharks, Scyliorhinus canicula (L.), from the southern Adriatic Sea importance for monitoring - Gajić, Andrej; Alić, Amer; Kahrić, Adla; Bilanović, Nurija; Šupić, Jovana; Beširović, Hajrudin (2020)
Melanomacrophages of fish are commonly explored as biomarkers of water pollution and are considered to be sensitive albeit non-specific health indicators in water ecosystems. Sharks as long living marine species are good sentinel species. This study presents morphometric data for splenic and hepatic melanomacrophages (MMC), and observed histopathology in ten lesser-spotted catsharks, Scyliorhinus canicula (L.), one of the most abundant shark species in the eastern Adriatic Sea. At necropsy, we collected random tissue samples from liver, brain, gallblader, pancreas, spleen, kidney, gills, entire digestive system, thyroid gland, rectal gland, entire urogenital (male samples) and genital system (female samples). Collected tissue samples were routinely processed and stained with hematoxylin-eosin, Periodic Acid-Schiff, and Masson Trichrome for microscopic examinations and morphometry. There was a minimal number of histopathological lesions in the examined sharks, but morphometric values reported herein were three folds higher than in previous studies in free-ranging sharks. Studies on larger numbers of sharks are needed to elucidate the biological significance of our finding in the context of population decline of the lesser-spotted catshark.
Melanomakrofagni centri različitih taksa ribolikih životinja nerijetko se koriste kao biomarkeri u ekološkim studijama, te se smatraju pouzdanim pokazateljima stanja u ispitivanju onečišćenja. Mor-ski psi, kao objektivno dugoživuće marinske vrste, predstavljaju idealne modele za ovakve studije. U ovom radu autori su prezentirali detaljne morfometrijske podatke za melanomakrofagne centre (MMC) opservirane u jetri i slezeni, kao i uočene histopatološke promjene na deset jedinki morske mačke bljedice, Scyliorhinus canicula (L.) - kao jedne od najzastupljenijih prečnousta istočnog Jadranskog mora. Tijekom obdukcije, uzorkovani su svi organi koji si potom rutinski histološki bojeni (hematoksilin-eozin, Periodic Acid-Schiff i Masson’s Trichtome) s ciljem detaljnijih mik-roskopskih opservacija. Uočena morfologija, kao i brojnost, MMC ispitivanih jedinki odgovara lit-eraturnim podacima za druge vrste prečnousta. Međutim, dokumentirane morfometrijske vrijednosti bile su tri puta veće u odnosu na prethodne studije. Prosječni broj MMC po vidnom polju (HPF) i prosječan postotak područja okupiranog od strne MMC u jetri i slezeni nisu pokazali statistički značajnu razliku. Ipak, prosječna površina jednog jetrenog MMC bila je veća u odnosu na one u slezeni (p<0,05). Opisani podaci o MMC značajno doprinose još uvijek dosta ograničenim podacima o distribuciji, morfologiji i morfometrija MMC kod landovine, te možemo reći da predstavljaju polaznu vrijednost za sljedeće studije. Daljnje, multidisciplinarne, studije neophodne su kako bi se ostvario širi uvid u učinke i povezanost MMC s različitim patološkim stanjima i razumijevanje nega-tivnog utjecaja pritisaka koji vladaju u staništu na zdravstveno stanje mačke bljedice, ali i drugih vrsta, u Jadranskom moru.
Bibliografija: str. 180-182.
Summary ; Sažetak.
Keywords: Morski psi -- Mačka bljedica -- Bolesti -- Melanomakrofagni centri -- Onečišćenje mora -- Monitoring; Jadransko more